Etude de Quelques Défauts Cathodiques dans une Pile à Combustible PEM - Maazouzi Atallah; Bouazzara Mebarek; BOUGRINE Mohamed (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE: DEPARTEMENT D’ÉLECTROTECHNIQUE, 2024)
In this study, some cathodic defects in PEM (Proton Exchange Mem brane) fuel cells are analyzed. The aim of this study is to identify and understand the impact of these defects on the performance and efficiency of the fuel cell. The work extends an existing simulator for fuel cells developed by Pukrushpan et al. to include the simulation of faults. The study also provides empirical suggestions on the distinguishability of these faults based on the simulation of the faults effect on some fuel cell outputs.
Automatique et Systèmes